2015
DOI: 10.1093/cercor/bhv073
|View full text |Cite
|
Sign up to set email alerts
|

Co-Activation-Based Parcellation of the Lateral Prefrontal Cortex Delineates the Inferior Frontal Junction Area

Abstract: The inferior frontal junction (IFJ) area, a small region in the posterior lateral prefrontal cortex (LPFC), has received increasing interest in recent years due to its central involvement in the control of action, attention, and memory. Yet, both its function and anatomy remain controversial. Here, we employed a meta-analytic parcellation of the left LPFC to show that the IFJ can be isolated based on its specific functional connections. A seed region, oriented along the left inferior frontal sulcus (IFS), was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 127 publications
6
51
0
4
Order By: Relevance
“…One proposed role of this region has been in coordinating the selection of the correct orthographic lexical representation among competing representations (Rapp & Lipka, 2011). This is in line with previous work associating it with cognitive control (Brass et al, 2005), and more recently it has been specifically associated with top-down control of linguistic functions (Muhle-Karbe et al, 2015). …”
Section: Discussionsupporting
confidence: 92%
“…One proposed role of this region has been in coordinating the selection of the correct orthographic lexical representation among competing representations (Rapp & Lipka, 2011). This is in line with previous work associating it with cognitive control (Brass et al, 2005), and more recently it has been specifically associated with top-down control of linguistic functions (Muhle-Karbe et al, 2015). …”
Section: Discussionsupporting
confidence: 92%
“…The brain region that showed the strongest correlations between modal controllability and creativity measures was a region in the right dorsolateral prefrontal cortex—the right Inferior Frontal Junction (IFJ). Located at the junction of the inferior frontal sulcus and the precentral sulcus (Muhle-Karbe et al, 2016), the left IFJ has been shown to play a general role in creative tasks (Gonen-Yaacovi et al, 2013) and has been specifically attributed to cognitive flexibility and task switching (Harding, Yücel, Harrison, Pantelis, & Breakspear, 2015; Yin, Wang, Pan, Liu, & Chen, 2016). Recently, Sebastian et al (2016) showed that the right IFJ was associated with the detection of salient stimuli and co-activated with both the ventral and dorsal attention networks (Corbetta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have focused on ascribing a particular process to an area or areas or interest (e.g., Aron et al, 2014; Banich, 2009; Botvinick, Cohen, & Carter, 2004; Muhle-Karbe et al, 2015; Stuss & Alexander, 2007). Others have taken a broader view, positing a rostral-caudal organization or hierarchy according to complexity or abstraction, a dorsal/ventral distinction by type of information, and a medial/lateral distinction related to emotional and motivational content (Badre & D’Esposito, 2009; Christoff & Gabrieli, 2000; Courtney, 2004; Fuster, 2001; Koechlin & Summerfield, 2007; Nee et al, 2013; O’Reilly, 2010; Petrides, 2005; Smith & Jonides, 1999).…”
Section: Neural Substratesmentioning
confidence: 99%